Interrelation of Individual-Personal Anti-Aging Strategies with Biological Age - T.N. Berezina; A.V. Litvinova; A.M. Zinatullina (Современная зарубежная психология, 2022)
The definition of anti-aging is given as a condition that reduces the biological age, improves health or increases life expectancy. Based on the meta-analysis, 13 anti-aging strategies were identified: sports, control, creative, intellectual, subject, altruistic, humor, self-improvement, risk, communication, interaction with nature, achievement, optimism. An empirical study of the effectiveness of these strategies has been carried out. Subjects: persons of retirement age, men — 61—70, women — 56—70 years. The following methods were used: diagnostics of biological age according to Voitenko, questionnaire of personal resources, assessment of individual typological features, correlation analysis. It was found out that the relationship of biological aging with personal resources depends on the socio-demographic characteristics of the individual. Conclusions: to develop an individual-personal anti-aging strategy, it is necessary to take into account the totality of data: gender, age, place of residence, family, children, physique, emotionality, functional asymmetry, interaction style. An effective anti-aging strategy is selected individually for each respondent.